The simplified expression of (5.1)(5.1^2)^4 is (5.1)^9
<h3>How to simplify the expression?</h3>
The expression is given as:
(5.1)(5.12)4
Rewrite the expression properly as follows:
(5.1)(5.1^2)^4
Rewrite the expression properly as follows:
(5.1)(5.1^2)^4 = (5.1) * (5.1^2)^4
Apply the power law of indices
(5.1)(5.1^2)^4 = (5.1) * (5.1^8)
Apply the power law of indices
(5.1)(5.1^2)^4 = (5.1)^(1 + 8)
Evaluate the sum
(5.1)(5.1^2)^4 = (5.1)^9
Hence, the simplified expression of (5.1)(5.1^2)^4 is (5.1)^9
Read more about expressions at
brainly.com/question/723406
#SPJ1